Ambient Moisture Accelerates Hydroamination Reactions of Vinylarenes with Alkali‐Metal Amides under Air. (28th August 2020) - Mulks, Florian F.; Bole, Leonie J.; Davin, Laia; Hernán‐Gómez, Alberto; Kennedy, Alan; García‐Álvarez, Joaquín; Hevia, Eva
Abstract: A straightforward alkali‐metal‐mediated hydroamination of styrenes using biorenewable 2‐methyltetrahydrofuran as a solvent is reported. Refuting the conventional wisdom of the incompatibility of organolithium reagents with air and moisture, shown here is that the presence of moisture is key in favoring formation of the target phenethylamines over competing olefin polymerization products. The method is also compatible with sodium amides, with the latter showing excellent promise as highly efficient catalysts under inert atmosphere conditions. Abstract : The nemesis of organo‐alkali‐metal reagents, that is, ambient moisture, can remarkably accelerate the alkali‐metal amide induced hydroamination of styrenes. A practically simple aerobic procedure for these hydroaminations under air and in renewable 2‐methyltetrahydrofuran is revealed.